A viseme recognition system using lip curvature and neural networks to detect Bangla vowels - Akhter, Nahid (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2016.